Health Information : A Survey Study of Rat Vector in the Working Area of The Port Health Office Class II, Tarakan City - Irayanti, Irayanti; Firmansyah, Yura Witsqa; Widyantoro, Wahyu; Pratama, Aziz Yulianto; Rachmawati, Ike; Lewinsca, Maurend Yayank; Ramadhansyah, Muhammad Fadli (Jurnal Rekam Medis & Manajemen Infomasi Kesehatan, 2022)
Rats are carriers and breeding grounds for a variety of parasites. The existence of a large population of rats can cause zoonotic diseases. This research is a survey and identification of the presence of rats in the Tarakan Class II Port Health Office Juwata Tarakan Airport and Port Working Area as an effort to prevent zoonotic disease caused by rat vectors. This research is descriptive with quantitative data types, measuring the presence of rats for 4 days and identification of rat species using survey and observation data collection methods. The results showed that the rats caught were still in low numbers with the types of rats caught being Rattus rattus and Rattus novergicus. Observation of the area showed that poor sanitation conditions, the density of piles of goods, sewerage, and the distance between the trash can and the canteen were opportunities for rats